Apoptosis-inducing effect of myxoma virus on human neuroglioma cell lines - Zhang, Qiu-Sheng (Exp Ther Med, 2017)
The purpose of this study was to further evaluate the role of myxoma virus (MYXV) as an oncolytic agent against experimental human gliomas in vitro, and analyze the effect of MYXV on malignant glioma cells at different incubation periods and infected at different multiplicities of infection. Neuroglioma cell lines U251 and A172 were cultured with various infective doses of myxoma virus at different time points (0–3 days) and cellular survival rates were evaluated using an MTT assay. Cell viability and cell death rates were assessed using Annexin V/propidium iodide and applying flow cytometry. Furthermore, the expression levels of phosphorylated AKT (p-AKT) in malignant gliomas were detected by western blot analysis to investigate the possible cell signaling targets in the pathway. MYXV exhibited a dose and time-dependent cytotoxic effect on neuroglioma cells, and there was increased expression of p-AKT in malignant gliomas. The present study confirms that MYXV induces oncolysis of malignant gliomas through regulating the activation of AKT. As such, MYXV is a potential therapeutic agent against human malignant gliomas.